2013
DOI: 10.4317/medoral.18220
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin B1 overexpression in conventional oral squamous cell carcinoma and verrucous carcinoma- A correlation with clinicopathological features

Abstract: Background: Nuclear localization of cyclin B1 is an indicator for cells undergoing mitotic division, and the overexpression has shown promising results as a good prognostic predictor for patients of squamous cell carcinoma (SCC). Cyclin B1 overexpression among histological grades of conventional oral squamous cell carcinoma (COSCC), as well as comparison with verrucous carcinoma (VC) has been less investigated. Study Design: Immunohistochemical expression of cyclin B1 was compared with various clinicopathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Meanwhile, P27 Kip1 is inversely related to GC and its decreased expression is reported as a negative prognostic marker in GC [ 89 – 91 ]. Cyclin B1 regulates the cell cycle transition from G2 to M phase [ 92 ] and plays key roles in cell differentiation, apoptosis, and metastasis [ 93 – 97 ]. And its expression might be relevant to the poor outcome of GC patients [ 98 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, P27 Kip1 is inversely related to GC and its decreased expression is reported as a negative prognostic marker in GC [ 89 – 91 ]. Cyclin B1 regulates the cell cycle transition from G2 to M phase [ 92 ] and plays key roles in cell differentiation, apoptosis, and metastasis [ 93 – 97 ]. And its expression might be relevant to the poor outcome of GC patients [ 98 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells often have an abnormal mitotic cycle. Cell proliferation, differentiation, senescence and apoptosis are closely related to the cell cycle regulatory machinery (51). The markers associated with the dysregulation of the cell cycle machinery usually indicate cancer progression.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…This detection point cannot detect whether the DNA is damaged, whereas the damaged DNA to continue to undergo mitosis; and it would also cause the proteasome to break down and recognize all MPF in the middle stage of division, resulting in continuous proliferation and development of tumor cells [50]. CCNB1 and squamous cells build on each other, allowing cancer cells to proliferate and differentiate, while new cancer cells promote the expression of CCNB1 to further increase [51]. Previous studies have reported that KIAA0101 overexpression in mammalian cells can prevent UV-induced apoptosis, suggesting its essential role in regulating DNA repair, cell proliferation, apoptosis and cell cycle progression [52].…”
Section: Discussionmentioning
confidence: 99%